MACHINE LEARNING TECHNOLOGIES IN BUSINESS PROCESS MANAGEMENT OF THE UNIVERSITY - Sergey Nikolaevich Tereshchenko (International Journal of Advanced Studies, 2019)
Machine learning technologies are developing rapidly. There is a tendency to simplify the availability of machine learning for various fields. As an example shows the process of admission of NSUEM entrants.